PEMBANGUNAN LINGKUNGAN BERKELANJUTAN DAN PENINGKATAN DAYA TARIK WISATA MELALUI PROGRAM KKN-TEMATIK DI DESA BASKARA BAKTI - Karsiningsih, Eni; Susmita Fita Monika; Rahayu; Sella Melisa; Nazifah; Herlinda Arika; Hasan ah Eka Risti; Salwazeela Septiani (Fakultas Pertania Universitas Muara Bungo, 2025)
Thematic Community Service Program (KKN-Tematik) is a form of community service carried out by students as part of the Tridharma of higher education. This program aims to contribute to village development and provide students with practical experience in applying their knowledge. In Baskara Bakti Village, the KKN-Tematik team is developing tourism potential through work programs such as creating green alleys, installing directional signs, and constructing a landmark monument as a tourist icon at Menuang Beach. The implementation of the Green Alley program aims to utilize the limited yard space of residents for reforestation and small-scale agriculture, contributing to local food sustainability and community resilience, while also serving as an attraction for local tourists. In addition, the installation of signs aims to improve accessibility and organization within the village, while the construction of the monument seeks to enhance the village's identity and tourist appeal. Through this work program, it is expected to support sustainable village development, increase community awareness of the environment, and enhance the village’s attractiveness as an eco-cultural tourism destination. This KKN program activity makes a tangible contribution to supporting sustainable village development and improving the welfare of the Baskara Bakti Village community.